Long‐term outcomes for different surgical strategies to treat left ventricular outflow tract obstruction in hypertrophic cardiomyopathy. (16th November 2017) - Collis, Richard; Watkinson, Oliver; O'Mahony, Constantinos; Guttmann, Oliver P.; Pantazis, Antonis; Tome‐Esteban, Maria; Tsang, Victor; Chandrasekaran, Venkatachalam; McGregor, Christopher G.A.; Elliott, Perry M.
Abstract : Aims: Surgical intervention is used to treat dynamic left ventricular outflow tract obstruction (LVOTO) in hypertrophic cardiomyopathy. This study assesses the effect of different surgical strategies on long‐term mortality and morbidity. Methods and results: In total, 347 patients underwent surgical intervention for LVOTO (1988–2015). Group A ( n = 272) underwent septal myectomy; Group B ( n = 33), septal myectomy and mitral valve (MV) repair; Group C ( n = 22), myectomy and MV replacement; and Group D ( n = 20), MV replacement alone. Median follow‐up was 5.2 years (interquartile range 1.9–7.9). The mean resting LVOT gradient improved post‐operatively from 71.9 ± 39.6 mmHg to 13.4 ± 18.5 mmHg ( P < 0.05). Overall, 72.4% of patients improved by >1 New York Heart Association (NYHA) class; 58.9% of patients undergoing MV replacement alone did not improve their NYHA class. There were 5 perioperative deaths and 20 late deaths (>30 days). Survival rates at 1, 5 and 10 years respectively were 98.4, 96.9, 91.9% in Group A; 97.0, 92.4, 61.6% in Group B; 100.0, 100.0, 55.6% in Group C; and 94.7, 85.3, 85.3% in Group D (log‐rank, P < 0.05). Long‐term (>30 days) complications included atrial fibrillation (29.6%), transient ischaemic attack/stroke (2.4%) and heart failure hospitalisation (3.2%). There were 16 repeat surgical interventions at 3.0 years. Conclusion: Septal myectomy is a safe procedure resulting in symptomatic improvement in the majority of patients. The annual incidence of non‐fatal disease‐related complications after surgical treatment of LVOTO is relatively high. Patients who underwent MV replacements had poorer outcomes with less symptomatic benefit in spite of a similar reduction in LVOT gradients.